2013
DOI: 10.1073/pnas.1222216110
|View full text |Cite
|
Sign up to set email alerts
|

Functional link between bone morphogenetic proteins and insulin-like peptide 3 signaling in modulating ovarian androgen production

Abstract: Bone morphogenetic proteins (BMPs) are firmly implicated as intraovarian regulators of follicle development and steroidogenesis. Here we report a microarray analysis showing that treatment of cultured bovine theca cells (TC) with BMP6 significantly (>twofold; P < 0.01) up-or down-regulated expression of 445 genes. Insulin-like peptide 3 (INSL3) was the most heavily down-regulated gene (−43-fold) with cytochrome P450, subfamily XVII (CYP17A1) and other key steroidogenic transcripts including steroidogenic acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 55 publications
10
72
0
Order By: Relevance
“…The ovarian hormone INSL3 plays an important role in maintaining androgen production by ovarian theca cells by inducing CYP17 steroidogenic enzyme [16] and modulates both LH and FSH actions [16], [17]. INSL3 is regulated by LH in ovarian theca cells [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ovarian hormone INSL3 plays an important role in maintaining androgen production by ovarian theca cells by inducing CYP17 steroidogenic enzyme [16] and modulates both LH and FSH actions [16], [17]. INSL3 is regulated by LH in ovarian theca cells [18].…”
Section: Resultsmentioning
confidence: 99%
“…INSL3 is a circulating peptide hormone of the relaxin-insulin family involved in tumor cell growth, differentiation, invasion and neovascularization [33]. INSL3 induces CYP17 expression in the ovary, maintaining androgen production [16]. The highest levels of INSL3 transcripts were found in group C endometriosis also aberrantly expressing the LHR, together with the strongest induction of the complete steroidogenic cascade, involving CYP17 and CYP11.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, INSL3 is constitutively secreted by adult Leydig cells and serves as a serum biomarker of this cell type (Anand-Ivell et al, 2009), although the function of INSL3 in the adult testis remains unclear (Ivell et al, 2013). Insl3 is also expressed in the ovary, particularly in theca interna cells of the maturing follicle (Satchell et al, 2013), where it induces androgen production (Glister et al, 2013). It is conceivable that serum levels of INSL3 could be a biomarker of post-GDX adrenocortical neoplasms, and future experiments will explore this possibility.…”
Section: Resultsmentioning
confidence: 99%
“…INSL3 has a critical role in testis descent, and INSL3 knockout mice are cryptorchid and infertile (Nef and Parada, 1999;Zimmermann et al, 1999). It plays an important role in gubernaculum development, which is involved in the first stage of testis descent, and also appears to have a role in the maintenance of ovarian function (Spanel-Borowski et al, 2001;Kawamura et al, 2004;Glister et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As INSL3 is a product of the thecal cells of ovarian follicles, plasma INSL3 levels have been investigated and shown to be elevated in polycystic ovary syndrome, a common female endocrine disorder characterized by excessive production of androgens from ovarian follicles (Gambineri et al, 2007;Szydlarska et al, 2012;Anand-Ivell et al, 2013). Importantly, a recent study in cows demonstrated that INSL3 has a positive autoregulatory role in maintaining thecal androgen production that is essential for normal ovarian follicle development (Glister et al, 2013).…”
mentioning
confidence: 99%